2002
DOI: 10.1128/iai.70.1.140-146.2002
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency of the Translocation ofMycobacterium tuberculosisacross a Bilayer of Epithelial and Endothelial Cells as a Model of the Alveolar Wall Is a Consequence of Transport within Mononuclear Phagocytes and Invasion of Alveolar Epithelial Cells

Abstract: The mechanism(s) by which Mycobacterium tuberculosis crosses the alveolar wall to establish infection in the lung is not well known. In an attempt to better understand the mechanism of translocation and create a model to study the different stages of bacterial crossing through the alveolar wall, we established a two-layer transwell system. M. tuberculosis H37Rv was evaluated regarding the ability to cross and disrupt the membrane. M. tuberculosis invaded A549 type II alveolar cells with an efficiency of 2 to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
144
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(151 citation statements)
references
References 18 publications
7
144
0
Order By: Relevance
“…On the other hand, previous studies showed that alveolar Type II epithelial cells and macrophages collaborate in the translocation of mycobacteria into distal lung parenchyma. 55 In addition, alveolar epithelial cell lines in culture are subject to necrosis by virulent but not attenuated mycobacterial organisms. 56,57 The attenuation of BCG is related to the loss of the RD1 locus encoding ESAT-6, which is responsible in part for the cytolysis of pneumocytes by virulent mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, previous studies showed that alveolar Type II epithelial cells and macrophages collaborate in the translocation of mycobacteria into distal lung parenchyma. 55 In addition, alveolar epithelial cell lines in culture are subject to necrosis by virulent but not attenuated mycobacterial organisms. 56,57 The attenuation of BCG is related to the loss of the RD1 locus encoding ESAT-6, which is responsible in part for the cytolysis of pneumocytes by virulent mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Cell culture studies using transwells have suggested that mycobacteria traverse epithelial barriers both within macrophages as well as directly [1,30]. In fact, the ESX-1/RD1 virulence determinant has been implicated in the ability of pathogenic mycobacteria to directly cross epithelial barriers [31].…”
Section: Step 3: Migration Of Infected Macrophages To Deeper Tissuementioning
confidence: 99%
“…However, a direct examination of mycobacterial transport in the zebrafish embryo has revealed that infecting mycobacteria traverse both endothelial and epithelial barriers mainly within macrophages in vivo; very little transit occurs in embryos lacking phagocyte lineages (created by morpholino knockdown of the myeloid transcription factor pu.1) [15]. The signals causing these infected macrophages to migrate back into deeper tissue to initiate granuloma formation are poorly understood [1] and this area is ripe for exploration in the zebrafish. For example, the function of chemokines important in migration of myeloid cells to and from the lung in mouse models may be dissected in greater detail in the zebrafish [32].…”
Section: Step 3: Migration Of Infected Macrophages To Deeper Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…This is further complicated by the lack of an effective vaccine (Russell et al, 2010), prolonged chemotherapy regimens (Mitchison & Davies, 2012) and adverse TB/HIV drug interactions (Luetkemeyer et al, 2011). Knowledge on the mechanisms utilized by M. tuberculosis to infect the host would offer novel perspective and define new targets to facilitate the design and development of drugs that are effective against both sensitive and resistant organisms (Ginsberg & Spigelman, 2007), efficacious vaccines (Bermudez et al, 2002), as well as crucially needed rapid, accurate and cheap point-of-care tests (Wallis et al, 2010).…”
Section: Introductionmentioning
confidence: 99%